2014
DOI: 10.1136/bmjopen-2014-006544
|View full text |Cite
|
Sign up to set email alerts
|

Prescriber barriers and enablers to minimising potentially inappropriate medications in adults: a systematic review and thematic synthesis

Abstract: ObjectiveTo synthesise qualitative studies that explore prescribers’ perceived barriers and enablers to minimising potentially inappropriate medications (PIMs) chronically prescribed in adults.DesignA qualitative systematic review was undertaken by searching PubMed, EMBASE, Scopus, PsycINFO, CINAHL and INFORMIT from inception to March 2014, combined with an extensive manual search of reference lists and related citations. A quality checklist was used to assess the transparency of the reporting of included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
681
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 571 publications
(739 citation statements)
references
References 61 publications
30
681
2
7
Order By: Relevance
“…For example, a 2013 Cochrane review [60] found that chronic antipsychotics used for neuropsychiatric symptoms of dementia can be safely withdrawn without detrimental effects on behaviour, and a recent randomized clinical trial found that withdrawal of statins in the setting of a life-limiting illness resulted in improved quality of life and reduced medication costs [61]. While it is still unknown what is the most effective way to implement deprescribing in practice [62], this term and a consistent definition will have important implications for both research and practice. While Woodward's seminal article [1] is the most highly cited, its definition consists of principles/steps for conducting deprescribing and only included four of the eight characteristics that were identified across all the included articles and therefore has not been employed consistently (even among the articles which cited it).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2013 Cochrane review [60] found that chronic antipsychotics used for neuropsychiatric symptoms of dementia can be safely withdrawn without detrimental effects on behaviour, and a recent randomized clinical trial found that withdrawal of statins in the setting of a life-limiting illness resulted in improved quality of life and reduced medication costs [61]. While it is still unknown what is the most effective way to implement deprescribing in practice [62], this term and a consistent definition will have important implications for both research and practice. While Woodward's seminal article [1] is the most highly cited, its definition consists of principles/steps for conducting deprescribing and only included four of the eight characteristics that were identified across all the included articles and therefore has not been employed consistently (even among the articles which cited it).…”
Section: Discussionmentioning
confidence: 99%
“…Previous deprescribing interventions have sometimes had little or no effect, 33 and there are multiple factors that shape both prescriber 34 and patient 35 barriers to deprescribing including complexity and time limitations, an underappreciation of the scale of polypharmacy-related harms, the increasing intensity of medical care in general, the fear of precipitating an acute event, and the conceptual difficulty involved in balancing risks and benefits. 3,13 Only 21% of the Choosing Wisely campaign's current recommendations refer to stopping specific medications.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on deprescribing in residential care settings, complex case examples, and understanding the views of patients. [21][22][23][24][25][26][27][28][29][30][31] We sought to explore the views of primary care physicians on the barriers to and facilitators of deprescribing in everyday practice to inform the development of an intervention to support safer prescribing.…”
Section: Introductionmentioning
confidence: 99%